2009
DOI: 10.1177/0305735608097248
|View full text |Cite
|
Sign up to set email alerts
|

The effect of piano lessons on the vocabulary and verbal sequencing skills of primary grade students

Abstract: A number of studies have reported positive associations between music experience and increased abilities in non-musical (e.g., linguistic, mathematical, and spatial) domains in children. These transfer effects continue to be probed using a variety of experimental designs. The major aim of this quasi-experimental study was to examine the effects of a scaffolded music instruction program on the vocabulary and verbal sequencing skills of two cohorts of second-grade students. One group ( n = 46) studied piano form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 98 publications
3
55
0
9
Order By: Relevance
“…Daily music training in kindergarten (compared to weekly training) has been linked with enhanced phonological awareness which supports early language and literacy skills (Moritz, Yampolsky, Papadelis, Thomson, & Wolf, 2013), though this study did not control for sociodemographic variables. In the early primary years, instrumental music lessons have been associated with improved vocabulary and verbal sequencing skills in those receiving piano lessons, compared to those who did not (Piro & Ortiz, 2009). …”
Section: Music As a Home Learning Activitymentioning
confidence: 97%
“…Daily music training in kindergarten (compared to weekly training) has been linked with enhanced phonological awareness which supports early language and literacy skills (Moritz, Yampolsky, Papadelis, Thomson, & Wolf, 2013), though this study did not control for sociodemographic variables. In the early primary years, instrumental music lessons have been associated with improved vocabulary and verbal sequencing skills in those receiving piano lessons, compared to those who did not (Piro & Ortiz, 2009). …”
Section: Music As a Home Learning Activitymentioning
confidence: 97%
“…Peut-être aussi pourrait-elle s'expliquer par le fait que les élèves provenaient d'un milieu aisé et que la plupart ne présentaient pas de difficulté majeure particulière : les origines socioéconomiques des élèves où ont été menées les études recensées sont plus diversifiées. Par ailleurs, nos résultats vont à l'encontre de ceux qui ont été obtenus par Piro et Ortiz (2009), où les élèves du groupe avec musique ont obtenu des scores significativement plus élevés en vocabulaire expressif que ceux du groupe contrôle. Cela pourrait s'expliquer par le fait que leur programme avait une durée de trois ans, comparativement à nos programmes qui n'ont duré que quatre mois environ ; peut-être qu'une exposition prolongée à l'apprentissage musical pourrait être plus bénéfique à certains égards.…”
Section: Discussion Des Résultatsunclassified
“…De plus, on observe parfois des résultats significativement plus élevés dans les groupes avec musique en ce qui concerne le vocabulaire, la lecture de pseudo-mots (p. ex. « rulipe ») et la morphosyntaxe (Moreno et coll., 2009 ;Piro et Ortiz, 2009 ;Register, Darrow, Standley et Swedberg, 2007). Dans certains cas, toutefois, les différences observées ne peuvent être attribuées uniquement à l'implication musicale (Cardarelli, 2003) ni observées chez l'ensemble des participants (Olson, 2003).…”
Section: Recension Des éCritsunclassified
See 1 more Smart Citation
“…Differences in white matter are reported in the anterior part of the corpus callosum and the arcuate fasciculus bilaterally (Patston, Kirk, Rolfe, Corballis, & Tippett, 2007). It is suggested that infra-structural changes accompanying music practice may benefit performance in other domains, such as attention and working memory (Piro & Ortiz, 2009 …”
Section: Neuro-imaging Studiesmentioning
confidence: 99%